STUDY OF EFFECTIVENESS IN SERVICES QUALITY OF PT GUNUNG KERINCI WISATA - Puti Intan Sari; Kusumo Bintoro (Jurnal Scientia, 2023)
This study aims to determine how effective quality service at PT. Mount Kerinci. Lack of service and quality management system that doesn't work at PT. Mount Kerinci Tourism, including driver services that are inactive or sometimes reckless, departure times that are often late or often stop at one place for too long, and the age of the car that is no longer operational is the background to the problems of this research. Researchers used a qualitative approach, which aims to determine the extent to which the effectiveness of PT. Mount Kerinci Tourism seen from HR planning management selection and recruitment management, HR training and development, evaluation management, compensation management and HR supervision management. The data used for this research are primary data and secondary data. The results of the research analysis using in-depth interviews with the actors involved in this study were directors, operational managers, personnel and drivers.